The firm under regret aversion - Udo Broll; Peter Welzel; Kit Pong Wong (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
We examine the economic behavior of the regret-averse firm under price uncertainty. We show that the global and marginal effects of price uncertainty on production are both positive (negative) when regret aversion prevails if the random output price is positively (negatively) skewed. In this case, high (low) output prices are much more likely to be seen than low (high) output prices. To minimize regret, the firm is induced to raise (lower) its output optimal level. The skewness of the price distribution as such plays a pivotal role in determining the regret-averse firm's production decision.
urn:nbn:de:bsz:14-qucosa-219229
Keywords: D21; D24; D81; 330; Production; Regret theory; Skewness; Uncertainty